5(x-2)=23-4x

Simple and best practice solution for 5(x-2)=23-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-2)=23-4x equation:


Simplifying
5(x + -2) = 23 + -4x

Reorder the terms:
5(-2 + x) = 23 + -4x
(-2 * 5 + x * 5) = 23 + -4x
(-10 + 5x) = 23 + -4x

Solving
-10 + 5x = 23 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-10 + 5x + 4x = 23 + -4x + 4x

Combine like terms: 5x + 4x = 9x
-10 + 9x = 23 + -4x + 4x

Combine like terms: -4x + 4x = 0
-10 + 9x = 23 + 0
-10 + 9x = 23

Add '10' to each side of the equation.
-10 + 10 + 9x = 23 + 10

Combine like terms: -10 + 10 = 0
0 + 9x = 23 + 10
9x = 23 + 10

Combine like terms: 23 + 10 = 33
9x = 33

Divide each side by '9'.
x = 3.666666667

Simplifying
x = 3.666666667

See similar equations:

| x+7=2x+18 | | 2x-3+5x=8(3x+5) | | 5n+3n=17+7 | | 3X+5Y+3Z=-22 | | g=(-7) | | h(t)=-16t^2+100t+5 | | 5x+12=2x+24 | | 1x+56=-7x+96 | | 7y-5=14y+23 | | -275+27x=16x+187 | | 5x-7=5+2x | | x+7y=49 | | 2x-3+5c=8(3x+5) | | x(x^2-10x+13)=0 | | 2.5c+7.5c=-25.5 | | 15-(4m+1)=4+4m-12 | | .20(2x-10)+4x=-3(.20x+4) | | (3r^2*4r)(3r^2*4r)=0 | | x+9=4x^2-2x+6 | | 1x+56=101-7x | | 4c-3=63 | | 4p-20=10p-14 | | 9-(-3k+3)=(k+3)+3 | | 12x+28=48x-44 | | x=16x | | 2v-9=8-3v | | 4c-80=3c-51 | | 3x+4(2x-9)=-14 | | -9(v+2)+4v+6=8v+7 | | 1-5x-4x=-80 | | 3(2c-3)-3=4c+6 | | -5-8=121 |

Equations solver categories